The discursive malleability of an identity: A dialogic approach to language "medium" schooling in North India - LaDousa, C. (Journal of Linguistic Anthropology, 2006)
This article employs a dialogic approach, in the parlance of Bakhtin, to explore the ways in which a school's "medium," its primary language of instruction, has become a major category of identity in North India. Many people describe themselves and others by invoking attendance at either a Hindi- or English-medium school. The first task of this article is to account for what Bakhtin calls "centripetal forces" that enable people at different positions in terms of class or school experience to use a common duality of Hindiversus English-medium and its attendant social resonances. The second task is to account for the abilities of a teacher to question the inevitability of the medium divide and to radically reframe what is important about schooling. Her abilities derive, in part, from her experiences with schools, attesting to Bakhtin's insight that centripetal forces in language are never total, and that centrifugal forces arise from complex engagements with institutions. © 2006 by the American Anthropological Association. All rights reserved.
Keywords: dept.ant

Living with multiple languages: multilingualism, identity, and belonging - Ladousa, Chaise (International Journal of Bilingual Education and Bilingualism, 2006)
Keywords: dept.ant